Design Parameters for a Research Prototype Contactor (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Rotating spiral contacting is a novel technologythat allows an excellent control of contacting between two ormore phases flowing countercurrently through spiralchannel. This method solve the issues can arise from mixingfluids by using the centrifugal effect to enforce the fluids toflow side by side in a narrow channel in parallel layerswithout mixing. In this work the wide channel model wasused to identify the design parameters for a researchprototype rotating spiral contactor, and examine theperformance within a wide range of operating conditions.The study included air – water system and started byselecting the optimum liquid layer thickness,  , that lead tooptimum specific throughput,*N  , and the appropriatemolar flow rate ratio, n q for absorption process. Drawingthe design envelope for pressure difference as a function ofchannel height was the best way of selecting the appropriatechannel height, h , and also study the effect of usingdifferent values of spiral angle, R sin . This later allowof selecting the suitable value of the distance betweenchannel revolutions, t . Finally, this work presents theeffect of using wide range of solute values, f ' on thepressure difference, phases flow rates, and the rotation ratefor fixed design parameters of a research prototype.